Preventing school disaffection, failure and dropout. The ESF projects "Last Round" and "Energy Start" - Silvia Dell'Anna; Dario Ianes (Firenze University Press, 2021)
Early school leaving is a very important issue in our country, both for its individual consequences and for the social and economic repercussions. The Covid-19 pandemic has exacerbated some existing trends, increasing risk factors and putting at greater risk of dropout some portions of the school population. The article reflects on the phenomenon of early school leaving and on intervention options, with particular reference to the period of COVID-19 emergency. Starting from the results of two project experiences conducted in 2020 in some secondary schools of the Autonomous Province of Bolzano, the contribution examines the protective and risk factors, the needs of students at risk, the contents and teaching strategies of interventions. Finally, it reflects on the different options for implementation, on monitoring and research.   Prevenire la disaffezione scolastica, l'insuccesso e l'abbandono. I progetti FSE "Last Round" ed "Energy Start" La dispersione scolastica rappresenta una questione di grande rilevanza nel nostro Paese, sia per le sue conseguenze individuali sia per le ricadute sociali ed economiche. La pandemia da Covid-19 ha acuito alcune tendenze già esistenti, ampliando i fattori di rischio e colpendo con maggiore intensità alcune porzioni di popolazione scolastica. L'articolo riflette sul fenomeno dell'abbandono scolastico precoce e sulle opzioni di intervento, con particolare riferimento al periodo di emergenza sanitaria. A partire dai risultati di due esperienze progettuali condotte nell'anno 2020 in alcune scuole secondarie delle Provincia Autonoma di Bolzano, il contributo prende in esame i fattori protettivi e di rischio, i bisogni dell'utenza a rischio di dispersione, i contenuti e le strategie didattiche degli interventi formativi. Infine, si riflette sulle differenti modalità di implementazione, sul monitoraggio e sulla ricerca.